1987
DOI: 10.1111/j.1651-2227.1987.tb10430.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulphasalazine and Sulphapyridine Serum Levels in Children to Mothers Treated with Sulphasalazine during Pregnancy and Lactation

Abstract: Serum concentrations of sulphasalazine and sulphapyridine were measured during the first week of life in 15 children whose mothers had been on sulphasalazine during pregnancy. The serum concentrations of sulphapyridine and sulphasalazine were similar in the children and their mothers at delivery. The elimination rate of the drugs in the newborn children was slow but the concentrations were not so high that a bilirubin displacing effect could be expected. In eight mothers who were breast-feeding and taking sulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(49 citation statements)
references
References 19 publications
0
46
0
3
Order By: Relevance
“…In eight mothers who were breastfeeding and taking sulfasalazine, analyses were done from mothers' serum, breast milk and serum from their children. The results showed that the amount of sulfasalazine and sulfa pyridine transferred to the child in the breast milk is negligible with regards to the risk of kernicterus [Eshjorner, 1987].…”
Section: Sulfasalazinementioning
confidence: 83%
“…In eight mothers who were breastfeeding and taking sulfasalazine, analyses were done from mothers' serum, breast milk and serum from their children. The results showed that the amount of sulfasalazine and sulfa pyridine transferred to the child in the breast milk is negligible with regards to the risk of kernicterus [Eshjorner, 1987].…”
Section: Sulfasalazinementioning
confidence: 83%
“…However, in a large scale series conducted among 181 pregnant women, there was no increase in the risk of having a baby with congenital anomaly (8). On the other hand, due to the potential anti-folate effect of sulfasalazine, ingestion of 2 mg folate in the prenatal period and during pregnancy is recommended (9).…”
Section: Resultsmentioning
confidence: 99%
“…It is recommended that breast-feeding mothers using 5-ASA should follow their children's bowel habits more carefully. Similarly, sulfasalazine is a safe drug in breast-feeding women (61,62).…”
Section: ) Aminosalicylatesmentioning
confidence: 99%
“…У 8 грудных младенцев СУЛЬФ отсутство-Международные и российские рекомендации по лечению ревматических заболеваний [72]. В другом исследовании определяли содержание метаболитов лекарства в грудном молоке у женщин, получавших более 2 мес 2 г/сут СУЛЬФ [73].…”
Section: лекарства назначение которых в период лактации считается беunclassified